The Ability of Writing Fairy Tales through the Implementation of Audio Visual Learning Media - Winarti Winarti; Mutia Febriyana; Enny Rahayu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to determine the application of audiovisual learning media to the ability to write fairy tales by fifth semester students of the Indonesian Language Education study program at FKIP UMSU for the 2019-2020 academic year. The sample in this study was set randomly so that the chosen class V A morning as the experimental class and class V B morning as the control class. The sample consisted of 46 students consisting of 30 people in the experimental class and 16 people in the control class. The research location is in the Indonesian Language Education Study Program FKIP UMSU on Jalan Mukhtar Basri No. 3 Medan. The results in this study are that there is a significant influence of audiovisual learning media on the ability to write fairy tales by fifth semester students of the Indonesian Language Study Program FKIP UMSU in the academic year 2019-2020. The method used in this study is an experimental method, while the instrument used is an essay test in the form of writing a fairy tale.